Native games with a global reach - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
The International Islamic University Malaysia (IIUM) organised its first indigenous world games (i-games) at its Gombak campus last week. This was the first of its kind among Malaysian universities and possibly among universities globally. It is befitting for IIUM to initiate the i-games given that some 7,000 of its students are foreigners from 115 countries. This means celebrating an immensely rich diversity beyond the conventional cultural activities of dances and songs, in the form of recreational sports that are of indigenous significance.